Comparison of anti-Müllerian hormone and antral follicle count in the prediction of ovarian response: a systematic review and meta-analysis - Yang Liu; Zhengmei Pan; Yanzhi Wu; Jiamei Song; Jingsi Chen (BMC, 2023)
Abstract Background Increasingly studies reported that the Anti-Müllerian hormone (AMH) seems to be a promising and reliable marker of functional ovarian follicle reserve, even better than the AFC test. Our study aimed to conduct a meta-analysis to assess the predictive value of AMH and AFC for predicting poor or high response in IVF treatment. An electronic search was conducted, and the following databases were used: PubMed, EMBASE, and the Cochrane Library (up to 7 May 2022). The bivariate regression model was used to calculate the pooled sensitivity, specificity, and area under the receiver operator characteristic (ROC) curve. Subgroup analyses and meta-regression also were used in the presented study. Overall performance was assessed by estimating pooled ROC curves between AMH and AFC. Results Forty-two studies were eligible for this meta-analysis. Comparison of the summary estimates for the prediction of poor or high response showed significant difference in performance for AMH compared with AFC [poor (sensitivity: 0.80 vs 0.74, P < 0.050; specificity: 0.81 vs 0.85, P < 0.001); high (sensitivity: 0.81 vs 0.87, P < 0.001)]. However, there were no significant differences between the ROC curves of AMH and AFC for predicting high (P = 0.835) or poor response (P = 0.567). The cut-off value was a significant source of heterogeneity in the present study. Conclusions The present meta-analysis demonstrated that both AMH and AFC have a good predictive ability to the prediction of poor or high responses in IVF treatment.